2010
DOI: 10.1590/s1679-62252010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Habitat partitioning, habits and convergence among coastal nektonic fish species from the São Sebastião Channel, southeastern Brazil

Abstract: Based on a fish survey and preliminary underwater observations, 17 "morphotypes" were identified that characterize the morphological diversity found within 27 nektonic fish species sampled at São Sebastião Channel. Such "morphotypes" were studied using an ecomorphological approach, with the intention to investigate similarities and differences in shape and habits. Underwater field observations were also performed, to verify if the lifestyle of these species, such as vertical occupation of the water column and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Most of these benthic fishes have elongate, cylinder and/or depressed bodies with disruptive coloration and more sedentary habits, while the nektobenthic fishes are more conspicuous, generally presenting laterally compressed and higher bodies, with better maneuverability due to body, caudal peduncle and fin designs, which are also associated with fins shapes and positions. Such fishes are capable to explore all of the tridimensional complexity of reef habitats (see Gibran, 2004Gibran, , 2007Gibran, , 2010 and are generally more widespread among the different habitats than the benthic species. For instance, the abundant small sized benthic blennioids and gobioids, both carnivores and herbivores/ detritivores characterize the shallow, warm and turbulent tops, being rare or absent in the deeper and colder habitats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of these benthic fishes have elongate, cylinder and/or depressed bodies with disruptive coloration and more sedentary habits, while the nektobenthic fishes are more conspicuous, generally presenting laterally compressed and higher bodies, with better maneuverability due to body, caudal peduncle and fin designs, which are also associated with fins shapes and positions. Such fishes are capable to explore all of the tridimensional complexity of reef habitats (see Gibran, 2004Gibran, , 2007Gibran, , 2010 and are generally more widespread among the different habitats than the benthic species. For instance, the abundant small sized benthic blennioids and gobioids, both carnivores and herbivores/ detritivores characterize the shallow, warm and turbulent tops, being rare or absent in the deeper and colder habitats.…”
Section: Discussionmentioning
confidence: 99%
“…These fishes frequently co-occur in reef communities, with several specific mechanisms enabling the long-term coexistence of these potential competitors (Schmitt & Coyer, 1982). Detailed studies involving such closely-related species can clarify their ecomorphological relationships and shifts in resource use in order to minimize interspecific competition (see Schoener, 1974;Gibran, 2010). The two small-sized serranids, S. flaviventris and S. baldwini, occur largely in the deeper habitats of the rocky reefs, where boulders and rubble accumulate increasing structural complexity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oliveira et al (2010) have demonstrated a high degree of correlation between morphological characteristics and the exploitation of the resources available in the environment, whereas others have found a weak relationship between the two variables (e.g., Clifton & Motta, 1998;Casatti & Castro, 2006). Some studies, such as that of Gibran (2010), who analyzed nektonic coastal species in southeastern Brazil, have emphasized the need to consider the differential effects of phylogenetic and historic factors in the structuring of fish communities. This is because the characteristics presented by a species may be intrinsic to its evolutive lineage, rather than reflecting morphological adaptations to its environment.…”
Section: Introductionmentioning
confidence: 99%